LUNG CARCINOMA: ITS PROFILE AND CHANGING TRENDS - Siddiqui, Saad; Ali, Mohammed Usman; Ali, Mahrukh Ayesha; Shah, Noreen; Nasreen, Shagufta (Journal of Ayub Medical College Abbottabad, 2010)
Background: Lung Carcinoma is the leading causes of morbidity and mortality worldwide with an incidence of 1.3 million cases per year. This study was undertaken to determine prevalence of various histological types of lung carcinoma and to analyse their changing trends with time. Methods: This is a retrospective analytical study. A total of 330 cases of lung carcinoma were analysed from 2003 to 2008. Cases from Khyber Pakhtunkhwa and Federally Administered Tribal Area (FATA) were included in this study. Furthermore, only cases of lung carcinoma were considered while other malignancies were excluded. Results: Squamous Cell carcinoma was found in 42.7% of cases. Overall male to female ratio was 2.67:1. Prevalence of Squamous Cell carcinoma increased from 32% to 57.9% while that of Small Cell carcinoma increased from 12% to 17.1%. Unspecified type showed a decrease from 36% to 5.3%. Increase in the prevalence of Squamous Cell carcinoma was found in both males and females while change in the prevalence of Small Cell carcinoma was found only in males. Conclusion: Squamous Cell carcinoma was the most prevalent variant of lung carcinoma in our region, followed by Adenocarcinoma. Male to female ratio across different histological patterns did not show significant variation. Increase in the prevalence of Squamous Cell carcinoma was statistically significant in both males and females while in case of Small Cell carcinoma change in its prevalence was also significant in males. Keywords: Lung Carcinoma, Squamous Cell carcinoma, Adenocarcinoma, prevalence, profile